2007
DOI: 10.1177/1088868307309606
|View full text |Cite
|
Sign up to set email alerts
|

On Being Both With Us and Against Us: A Normative Conflict Model of Dissent in Social Groups

Abstract: Although past research has demonstrated a positive relationship between collective identification and normative conformity, there may be circumstances in which strongly identified members do not conform but instead choose to challenge group norms. This article proposes a normative conflict model, which distinguishes between nonconformity due to dissent (challenging norms to change them) and nonconformity due to disengagement (distancing oneself from the group). The normative conflict model predicts that strong… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

21
393
0
14

Year Published

2010
2010
2017
2017

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 254 publications
(428 citation statements)
references
References 136 publications
(205 reference statements)
21
393
0
14
Order By: Relevance
“…Falomir-Pichastor, Mugny, and Gabarrot proposed the notion of loyalty conflict to account for this conflicting state (Falomir-Pichastor, Gabarrot & Mugny, 2009a, 2009b; see also , and suggested that high identifiers solve this conflict by opposing the egalitarian norm (i.e., they show non-conformity or even counter-conformity) paradoxically as a way to show their loyalty to the group (see also Jetten & Hornsey, 2013;Packer, 2008). In a series of experimental studies.…”
Section: Group Identification and Conflicting Motivesmentioning
confidence: 99%
“…Falomir-Pichastor, Mugny, and Gabarrot proposed the notion of loyalty conflict to account for this conflicting state (Falomir-Pichastor, Gabarrot & Mugny, 2009a, 2009b; see also , and suggested that high identifiers solve this conflict by opposing the egalitarian norm (i.e., they show non-conformity or even counter-conformity) paradoxically as a way to show their loyalty to the group (see also Jetten & Hornsey, 2013;Packer, 2008). In a series of experimental studies.…”
Section: Group Identification and Conflicting Motivesmentioning
confidence: 99%
“…Basically, children learn the dos and don'ts of their parents, which in turn affects their behaviour within the society at large. Children naturally seek to be accepted by their family and society (McClelland, 1987;Packer, 2008). Young adults who have a strong need for affiliation enjoy being part of a group and tend to conform to the group's norms in order to be accepted by other members of the group (Christensen, Rothgerber, Wood, & Matz, 2004;McClelland, 1987;Packer, 2008;Smith & Mackie, 2007;Smith, Hogg, Martin, & Terry, 2007).…”
Section: Parents' Participationmentioning
confidence: 99%
“…The dissenting opinions that are needed for effective design will be more likely to be expressed if the climate of the team is one that supports and encourages positive deviance (Packer, 2008). Lencioni (2005) suggests that teams ask themselves "What is the dynamic we want in this team?…”
Section: Managing Team Conflictmentioning
confidence: 99%
“…Esser (1998) describes how pressure for conformity and the desire to preserve harmony within a team can inhibit the critical appraisal of relevant facts, thereby leading to poor decisions. Packer (2008) studied the relevant concept of positive deviance. Packer found that dissenting opinions may be more likely expressed if the culture/identity of the group dictates that such deviance is approved of and if dissenting individuals identify strongly with the group.…”
Section: Shared Understandingmentioning
confidence: 99%